Respuesta :

Answer:p = -1.25

Step-by-step explanation:

Simplifying

3 + 17p = -32 + -11p

Solving

3 + 17p = -32 + -11p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '11p' to each side of the equation.

3 + 17p + 11p = -32 + -11p + 11p

Combine like terms: 17p + 11p = 28p

3 + 28p = -32 + -11p + 11p

Combine like terms: -11p + 11p = 0

3 + 28p = -32 + 0

3 + 28p = -32

Add '-3' to each side of the equation.

3 + -3 + 28p = -32 + -3

Combine like terms: 3 + -3 = 0

0 + 28p = -32 + -3

28p = -32 + -3

Combine like terms: -32 + -3 = -35

28p = -35

Divide each side by '28'.

p = -1.25

Simplifying

p = -1.25

ACCESS MORE